Mcgraw-Hill reader : - Muller, Gilbert (McGraw-Hill, 2006)
Present an extensive overview of the critical thinking, reading and writing processes, extensive coverage of argument and persuasion, concise guide to research and documentation in the electronic age, liberal arts discipliné, including education, the social sciences, business and economics, the humanities and the sciences.